2004
DOI: 10.1213/01.ane.0000101987.79454.bc
|View full text |Cite
|
Sign up to set email alerts
|

Combined Spinal-Epidural Anesthesia Using Epidural Volume Extension Leads to Faster Motor Recovery After Elective Cesarean Delivery: A Prospective, Randomized, Double-Blind Study

Abstract: When compared with conventional, single-shot spinal anesthesia, epidural volume extension of a small-dose spinal block provides satisfactory anesthesia for cesarean delivery with only 55% of the bupivacaine dose required and is associated with faster motor recovery of the lower limbs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
73
3
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 20 publications
2
73
3
2
Order By: Relevance
“…15 Eileen et al showed that lower dose of 5 mg of intrathecal hyperbaric 0.5% bupivacaine with fentanyl 10µg followed by epidural volume extension (EVE) with 6 ml of 0.9% saline provide similar quality of anesthesia as that provided by higher dose of 9 mg of intrathecal hyperbaric 0.5% bupivacaine with fentanyl 10µg without EVE while allowing faster motor recovery of the lower limb. 16 As many previous studies supported the dose lowering effect of EVE of our study but Beagle et al who found that EVE has no significant or reliable dose lowering effect on intrathecal dose of bupivaciane. 17 This could be a result of small sample size chosen in this study (30 cases in each group) with only 50% achieving effective dose.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…15 Eileen et al showed that lower dose of 5 mg of intrathecal hyperbaric 0.5% bupivacaine with fentanyl 10µg followed by epidural volume extension (EVE) with 6 ml of 0.9% saline provide similar quality of anesthesia as that provided by higher dose of 9 mg of intrathecal hyperbaric 0.5% bupivacaine with fentanyl 10µg without EVE while allowing faster motor recovery of the lower limb. 16 As many previous studies supported the dose lowering effect of EVE of our study but Beagle et al who found that EVE has no significant or reliable dose lowering effect on intrathecal dose of bupivaciane. 17 This could be a result of small sample size chosen in this study (30 cases in each group) with only 50% achieving effective dose.…”
Section: Discussionsupporting
confidence: 65%
“…They thought this is unlikely as other studies had demonstrated the effect with lower dose of EVE only 5 ml and 6 ml EVE. 13,16 To avoid these bias we had selected a dose of 10 ml and colloid (6% HES) in place of crystalloid. As previous studies showed that colloid has more viscosity, absorbed slowly so may be more effective than crystalloid as EVE for enhancing spinal block.…”
Section: Discussionmentioning
confidence: 99%
“…Using EVE with saline, small-dose spinal block can be extended to provide adequate anesthesia for cesarean delivery 4 . Several mechanisms were reported to play a role in the enhancement of spinal block by EVE with saline, including the volume effect, in which the theca is compressed by epidural saline, resulting in the squeezing of cerebrospinal fl uid and more extensive spread of subarachnoid local anesthetic 5,6,8,12 .…”
Section: Discussionmentioning
confidence: 99%
“…The spinal component provides rapid onset of anesthesia and the drugs that are administered through the catheter placed in the epidural space maintain analgesia during the postoperative period 1 . The epidural volume extension (EVE) technique is a modifi cation of CSEA in which the level of sensory analgesia obtained via subarachnoid block is increased by a small volume of saline or local anesthetic administered through the epidural catheter [2][3][4][5][6] . The level of sensory block obtained is not only related to the analgesic effect of the local anesthetic administered into the epidural space, but to the effect of the volume of the epidural solution causing cephalic movement of the local anesthetic in the subarachnoid space 5,[7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…The combined sequential spinal epidural (CSSE) technique has been studied mostly for cesarean section, and it may be advantageous as well in other high-risk patients such as very old urologic patients, by increasing the safety of the central regional block . 6,19,20,21,22 Doses and concentrations of local anesthetic used for CSSE are of great importance in determining the clinical management of this technique, and local anesthetic pharmacodynamics and pharmacokinetic profile can influence CSSE outcome: recently Levobupivacaine emerged in regional anesthesia as a safer alternative to other local anesthetics, including its racemic parent bupivacaine, since it demonstrated less affinity and reduced depressant effects onto myocardial and central nervous vital centers in pharmacodynamics studies, and a superior pharmacokinetic profile 23 . Actually, CSSE with intrathecal dose of bupivacaine as low as 5 mg has been found to allow good surgical anesthesia in cesarean delivery 24 .…”
mentioning
confidence: 99%